2001
DOI: 10.1097/00006231-200108000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of ‘ecstasy’ abuse on the human brain studied by FDG PET

Abstract: The popular recreational drug, 'ecstasy', mainly contains 3,4-methylenedioxymethamphetamine (MDMA) as the psychotropic agent. MDMA is suspected of causing neurotoxic lesions to the serotonergic system as demonstrated by animal studies, examinations of human cerebrospinal fluid, and the first positron emission tomography (PET) studies using the serotonin transporter ligand [11C]-McN5652. Damage of serotonergic afferents might mediate long-lasting alterations of cerebral glucose metabolism as a secondary effect.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
49
1
3

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 34 publications
9
49
1
3
Order By: Relevance
“…Although this study and some other studies showed that adverse effects of a low ecstasy dose are limited (Downing, 1986;Vollenweider et al, 1998), there are various factors (eg, poor metabolism, hypertension, young age, simultaneous use of other substances, environmental conditions) that might contribute to individual or situational vulnerability for acute adverse effects and long-term neurotoxicity of ecstasy (Buchert et al, 2001;Obrocki et al, 2002;Green et al, 2004;Segura et al, 2005). Therefore, it is not possible to state that incidental use of ecstasy is completely safe.…”
Section: Discussionmentioning
confidence: 64%
“…Although this study and some other studies showed that adverse effects of a low ecstasy dose are limited (Downing, 1986;Vollenweider et al, 1998), there are various factors (eg, poor metabolism, hypertension, young age, simultaneous use of other substances, environmental conditions) that might contribute to individual or situational vulnerability for acute adverse effects and long-term neurotoxicity of ecstasy (Buchert et al, 2001;Obrocki et al, 2002;Green et al, 2004;Segura et al, 2005). Therefore, it is not possible to state that incidental use of ecstasy is completely safe.…”
Section: Discussionmentioning
confidence: 64%
“…A single study of resting metabolism in a large cohort of MDMA users (reviewed below) revealed significantly lower metabolic rate in bilateral caudate and putamen and left amygdala (Buchert et al 2001;Obrocki et al 2002) but these regions did not show gray matter alterations in the Cowan et al (2003) VBM study. Chang et al (2000), in their previously mentioned CBF study, detected a negative correlation between duration of MDMA use and global brain volume, but overall found no differences between MDMA users and controls in global brain volume, global cerebrospinal fluid (CSF), and percent CSF.…”
Section: Brain Volumementioning
confidence: 99%
“…Because basic research findings have associated MDMA exposure with specific long-term effects on 5-HT function, neuroimaging studies in human MDMA users have directly assayed components of the 5-HT system (McCann et al 1998;Semple et al 1999;Reneman et al 2000aReneman et al ,b, 2001aReneman et al , 2002cBuchert et al 2004;de Win et al 2004;McCann et al 2005), have assessed brain structure or function potentially altered as a secondary consequence of perturbed 5-HT function, or have examined brain regions implicated in MDMA-induced cognitive alterations (Chang et al 1999(Chang et al , 2000Obrocki et al 1999Obrocki et al , 2002Buchert et al 2001;Gamma et al 2001;Obergriesser et al 2001;Reneman et al 2001dReneman et al ,e, 2002dCowan et al 2003;Daumann et al 2003aDaumann et al ,b, 2004aDaumann et al ,b, 2005Jacobsen et al 2004;Moeller et al 2004;reviewed in Morgan 2000;Parrott 2001;Montoya et al 2002). This review examines currently available findings in the context of putative 5-HT toxicity and/or functional alterations with regard to brain structure and physiology.…”
Section: Introductionmentioning
confidence: 99%
“…Regions of interest (ROIs) were chosen according to ROIs described in humans [26,32]. Twelve ROIs were manually drawn on coronal sections: cerebellum, brain stem, thalamus, hippocampus, caudate-putamen, frontal cortex, amygdala, somatosensory cortex, visual cortex, auditory cortex, superior colliculus and whole brain.…”
Section: Animals Drug Administration and Experimental Protocolmentioning
confidence: 99%
“…Several markers for these systems (SERT, 5-HT 1A , 5-HT 2A ) are currently being investigated [24,25]. Buchert et al have proposed that MDMA-induced functional alterations of the serotonergic system may affect the glucose metabolism of cortical and subcortical structures [26]. However, possible effects of MDMA on regional brain glucose metabolism and blood glucose levels have received relatively little attention.…”
Section: Introductionmentioning
confidence: 99%